(untitled) (Repertorio Científico, 2022)
That paper presents the procedure and results of a bioassay performed with larvae of Pacific oyster Crassostrea gigas. Challenging it with a strain of Vibrio alginolyticus, Isolated from a sample of dead larvae. The evolution of the clinical sign and injuries progress of infection during the first 24 hours and the bacteriological analyzes are described. The mortality of the challenged groups exceeded 90%. Final bacterial counts exceeded 2.7x104cfu/ml. The strains recovered from the dead organisms are similar to those used in the infectious inoculum. Allowing establishing the causality of this strain with the mortalities observed in a production tank. Keywords. Bivalve molluscs, mortalities, Vibrio alginolyticus, pathogenicity, causality.